Operation Jihadi Bride : My Covert Mission to Rescue Young Women from ISIS - The Incredible True Story /: My Covert Mission to Rescue Young Women from ISIS - The Incredible True Story. (2019) - Carney, John; Thurlow, Clifford
No abstract available